Analisis Penerapan Eleman Keimanan Dan Ketakwaan Dalam Pembangunan Diri Badiuzzaman Said Nursi - Norullisza Khosim; Mohd Shukri Hanapi; Ahmad Luqman Ayob (Academic Inspired Network, 2025)
Indexed by MyCite